A 10-Year Single-Center Experience With the GORE TAG Conformable Thoracic Stent Graft in the Treatment of Thoracic Aortic Disease. (June 2022) - Skrypnik, Denis; Bischoff, Moritz S.; Meisenbacher, Katrin; Kronsteiner, Dorothea B.; Böckler, Dittmar
Objective: The aim of this study was to report 10-year real-world single-center experience with the GORE TAG conformable thoracic aortic graft (CTAG), focusing on rupture-free survival, aortic-related reintervention, and device-related complications during midterm and long-term follow-up (FU). Methods: This retrospective study analyzes results of thoracic endovascular aortic repair (TEVAR) performed between January 2009 and December 2018. Out of 419 TEVAR procedures within this period, 194 patients (male 57.2%, 111/194), with a mean age of 65 ± 13 years, were treated with the CTAG device. Indication for TEVAR was a thoracic aortic aneurysm in 24.7% (48/194), type B aortic dissection in 32.5% (63/194), penetrating aortic ulcer 15.5% (30/194), and miscellaneous 27.3% (53/194). Emergently were operated 43.8% (85/194) patients. Median follow-up (FU) including computed tomography imaging was 43.5 months (Q1-Q3: 8.6–67.0) and was completed in 91.2% (177/194) of patients. Results: Overall survival rates were 75.8% (95% confidence interval [CI] = [0.76–0.70]) and 56.6% (95% CI = [0.57–0.50]) at 12 and 60 months, respectively. Cumulative incidence for aortic rupture was 11.9% (95% CI = [0.07–0.17]) at 60 and 90 months, respectively. Cumulative incidence for aortic-related reintervention was 27.5% (95% CI = [0.21–0.34]) at 60 and 90 months. Cumulative incidence for migration was 2.8% (95% CI = [0.004–0.05]) and 3.9% (95% CI = [0.007–0.07]) at 60 and 90 months, respectively. New endograft infections or material fatigue were not observed. Conclusions: The herein reported 10-year real-world single-center experience with the CTAG observed favorable long-term outcome. Thus, the device demonstrates appropriate persistent safety, efficacy, and clinical durability up to long-term FU in the treatment of diverse thoracic aortic pathologies.